Efficacy and biomarker analysis of CD133-directed CAR T cells in advanced hepatocellular carcinoma: a single-arm, open-label, phase II trial. (1st January 2020) - Dai, Hanren; Tong, Chuan; Shi, Daiwei; Chen, Meixia; Guo, Yelei; Chen, Deyun; Han, Xiao; Wang, Hua; Wang, Yao; Shen, Pingping
ABSTRACT: Expressed by cancer stem cells of various epithelial cell origins and hepatocellular carcinoma (HCC), CD133 is an attractive therapeutic target for HCC. The marker CD133 is highly expressed in endothelial progenitor cells (EPC). EPCs circulate in increased numbers in the peripheral blood of patients with highly vascularized HCC and contribute to angiogenesis and neovascularization. This phase II study investigated CD133-directed chimeric antigen receptor (CAR) T (CART-133) cells in adults with HCC. Patients with histologically confirmed and measurable advanced HCC and adequate hematologic, hepatic, and renal functions received CART-133 cell infusions. The primary endpoints were safety in phase I and progression-free survival (PFS) and overall survival (OS) in phase II. Other endpoints included biomarkers for CART-133 T cell therapy. Between June 1, 2015, and September 1, 2017, this study enrolled 21 patients who subsequently received CART-133 T cells across phases I and II. The median OS was 12 months (95% CI, 9.3–15.3 months) and the median PFS was 6.8 months (95% CI, 4.3–8.4 months). Of 21 evaluable patients, 1 had a partial response, 14 had stable disease for 2 to 16.3 months, and 6 progressed after T-cell infusion. The most common high-grade adverse event was hyperbilirubinemia. Outcome was correlated with the baseline levels of vascular endothelial growth factor (VEGF), soluble VEGF receptor 2 (sVEGFR2), stromal cell-derived factor (SDF)-1, and EPC counts. Changes in EPC counts, VEGF, SDF-1, sVEGFR2, and interferon (IFN)-γ after cell infusion were associated with survival. In patients with previously treated advanced HCC, CART-133 cell therapy demonstrates promising antitumor activity and a manageable safety profile. We identified early changes in circulating molecules as potential biomarkers of response to CART-133 cells. The predictive value of these proangiogenic and inflammatory factors as potential biomarkers of CART-133 cell therapy in HCC will be explored in prospective trials. This study is registered at ClinicalTrials.gov (NCT02541370)